Comparative Analysis of Nanoparticle-Antibody Conjugations: Carbodiimide Versus Click Chemistry - Daniel L.J. Thorek; ew R. Elias; Andrew Tsourkas (Molecular Imaging)
The ability to modify the physical, chemical, and biologic properties of nanoparticles has led to their use as multifunctional platforms for drug delivery and diagnostic imaging applications. Typically, these applications involve functionalizing the nanoparticles with targeting agents. Antibodies remain an attractive choice as targeting agents because of their large epitope space and high affinity; however, implementation of antibody-nanoparticle conjugates is plagued by low coupling efficiencies and the high cost of reagents. Click chemistry may provide a solution to this problem, with reported coupling efficiencies nearing 100%. Although click chemistries have been used to functionalize nanoparticles with small molecules, they have not previously been used to functionalize nanoparticles with antibodies. Concerns associated with extending this procedure to antibodies are that reaction catalysts or the ligands required for cross-linking may result in loss of functionality. We evaluated the efficiency of conjugations between antibodies and superparamagnetic iron oxide nanoparticles using click chemistry as well as the functionality of the product. The results were compared with conjugates formed through carbodiimide cross-linking. The click reaction allowed for a higher extent and efficiency of labeling compared with carbodiimide, thus requiring less antibody. Further, conjugates prepared via the click reaction exhibited improved binding to target receptors.